Family Factors and Risk Sexual Behaviour in Students Aged 12-18 - Joana Simeonova; Nevena Tzvetanova; Yanka Tzvetanova (Journal of Biomedical & Clinical Research)
The aim of this study was to identify family factors determining risk sexual behavior among students aged 12- 18 in Veliko Turnovo region. A cross-sectional study was conducted in 2014. Three hundred and ten students were included in a representative sample of students attending seven schools in Veliko Turnovo region. The respondents filled in a self-administered questionnaire, designed to collect data on family interactions, acts of sexual coercion, parental social status and their influence on the sexual behavior of the students. Data were processed using SPSS.v.19. Parametric and non-parametric statistical methods were applied. About one-fifth of the students were nurtured in incomplete families. History of a sexually transmitted diseases correlated with type of family (p